PENERAPAN LITERASI MEMBACA BERBASIS PENELITIAN TINDAKAN KELAS UNTUK MENINGKATKAN PEMAHAMAN BACAAN SISWA - Yulianti, Nidha; Takiddin, Takiddin (Elementar : Jurnal Pendidikan Dasar, 2024)
The purpose of this study was to determine the application of reading literacy to improve students' reading comprehension skills in class III Indonesian at SD Muhammadiyah 12 Setiabudi Pamulang. This type of research is classroom action research (CAR), with two cycles. The instruments used to test students' reading comprehension skills used observation sheets and test questions. The subjects in this study were 33 class III students at SD Muhammadiyah 12 Setiabudi Pamulang. The data analysis technique used is descriptive statistics with percentages. Based on the results of research and discussion, it is known that the results of completeness in the pre-cycle are 72%, and completeness in cycle I is 76%, and completeness in cycle II is 84%. Based on these results it can be concluded that there is an increase in students' reading comprehension skills in Indonesian subjects by applying reading literacy.